(untitled) (Constructionism Conference Proceedings, 2025)
Maker Education and STEM+ initiatives are often celebrated for fostering creativity, problem-solving, and innovation. However, as these approaches gain global traction and the Maker Education movement matures, its technocentric underpinnings are increasingly critiqued for overshadowing deeper pedagogical aims. This paper examines initial insights from qualitative interviews with Maker educators and researchers, highlighting challenges and strategies for shifting Maker Education from a focus on tools and spaces towards pedagogies that prioritise the significance and centrality of community for learning, as well as a mindset of resistance to failure and a resilient approach to problem-solving. By re-centering constructionist ideas of creativity, iteration, and human connection, the findings demonstrate how community-centric practices can transform makerspaces into inclusive ecosystems of collaboration and growth. This work contributes actionable recommendations for embedding Maker Education into diverse educational settings, in the context of contemporary constructionism and in line with the conference’s theme of “Building Communities, Bridging Ideas.”